(untitled) (Journal of Tourism and Hospitality Education, 2020)
The agritourism (AT) concept in Nepal is growing. However, a proper definition based on the characteristics of the Nepalese economy and agriculture has not been given previously. Therefore, this study aims to define AT based on the Nepalese geographical division. Based on the secondary data, the author fist presented the definition of AT in international society and compared the AT between developed countries and developing countries. Then, the definition of AT based on the three geographical locations of Nepal i.e., Himalayan, Hilly, and Terai region, is given. For the successful Nepalese AT, the target should be given to the trekkers and hikers.